Identifikasi Kelas Kata Terbuka dalam Album Lagu Untuk Dunia, Cinta, dan Kotornya Karya Nadin Amizah Serta Struktur Makna - Nazwa Ramadhani (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the words structure of two selected songs, “Kekal” and “Di Akhir Perang”, from Nadin Amizah’s album Untuk Dunia, Cinta, dan Kotornya, with a focus on identifying and interpreting the functions of open class words and closed class words within the lyrical composition. The background of this research lies in the growing interest in understanding how contemporary Indonesian songwriters construct meaning through linguistic choices that contribute to the emotional depth of their works. The objective of this study is to analyze how open class words such as nouns, verbs, adjectives, and adverbs contribute to semantic imagery, while closed class words such as pronouns, conjunctions, prepositions, and aspects establish grammatical cohesion and narrative continuity. Using qualitative descriptive methods, the lyrics were segmented, categorized, and interpreted based on linguistic theory to reveal the semantic and grammatical roles of each word class. The findings show that open class words dominate the emotional and metaphorical landscape of the songs, functioning as carriers of imagery, personal vulnerability, and symbolic representation of healing, love, and existential reflection. Meanwhile, closed class words serve as structural anchors that link ideas, mark relationships between clauses, and maintain narrative fluidity, particularly in expressing inner conflict and the resolution of emotional war depicted in the lyrics. The study concludes that Nadin Amizah’s lyricism is not only aesthetically expressive but also linguistically strategic, revealing a deliberate interplay between lexical creativity and grammatical precision. These findings imply that linguistic analysis can enrich the appreciation of contemporary Indonesian music and open new perspectives for future studies in stylistics, discourse analysis, and cultural semantics.